Development and Validation of Prediction Models and Risk Calculators for Posthepatectomy Liver Failure and Postoperative Complications Using a Diverse International Cohort of Major Hepatectomies - Jane Wang; Jean Feng; Camilla Gomes; Lucia Calthorpe; Amir Ashraf‐Ganjouei; Fernanda Romero‐Hernández; Andrea Benedetti Cacciaguerra; Taizo Hibi; Mohamed A. Adam; Adnan Alseidi; Mohammad Abu Hilal; Nikdokht Rashidian (2023)
The study aim was to develop and validate models to predict clinically significant posthepatectomy liver failure (PHLF) and serious complications [a Comprehensive Complication Index (CCI)>40] using preoperative and intraoperative variables.